2023
DOI: 10.3390/plants12101959
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Functionalized Multiwall Carbon Nanotubes with Fe and Mn Oxides on Lactuca sativa L.

Dorina Podar,
Camelia-Loredana Boza,
Ildiko Lung
et al.

Abstract: The aim of this work was to evaluate the effect of six nanomaterials, namely CNT-COOH, CNT-MnO2, CNT-Fe3O4, CNT-MnO2-Fe3O4, MnO2, and Fe3O4 on lettuceTo determine the impact of nanomaterials on lettuce, the results obtained were compared with those for the control plant, grown in the same conditions of light, temperature, and humidity but without the addition of nanomaterial. The study found that the content of bioactive compounds and the antioxidant capacity varied in the treated plants compared to the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The synthesis and characterization of the nanoparticles used in this study were reported in the previous papers [23][24][25], as well as the cultivation conditions [26,27].…”
Section: Plant Growth Conditionsmentioning
confidence: 99%
“…The synthesis and characterization of the nanoparticles used in this study were reported in the previous papers [23][24][25], as well as the cultivation conditions [26,27].…”
Section: Plant Growth Conditionsmentioning
confidence: 99%